COXIBs and 2,5-dimethylcelecoxib counteract the hyperactivated Wnt/β-catenin pathway and COX-2/PGE2/EP4 signaling in glioblastoma cells - Aleksandra Majchrzak-Celińska; Julia O. Misiorek; Nastassia Kruhlenia; Lukasz Przybyl; Robert Kleszcz; Katarzyna Rolle; Violetta Krajka-Kuźniak (BMC Cancer, 2021)
Abstract Background Glioblastoma (GBM) is the deadliest and the most common primary brain tumor in adults. The invasiveness and proliferation of GBM cells can be decreased through the inhibition of Wnt/β-catenin pathway. In this regard, celecoxib is a promising agent, but other COXIBs and 2,5-dimethylcelecoxib (2,5-DMC) await elucidation. Thus, the aim of this study was to analyze the impact of celecoxib, 2,5-DMC, etori-, rofe-, and valdecoxib on GBM cell viability and the activity of Wnt/β-catenin pathway. In addition, the combination of the compounds with temozolomide (TMZ) was also evaluated. Cell cycle distribution and apoptosis, MGMT methylation level, COX-2 and PGE2 EP4 protein levels were also determined in order to better understand the molecular mechanisms exerted by these compounds and to find out which of them can serve best in GBM therapy. Methods Celecoxib, 2,5-DMC, etori-, rofe- and valdecoxib were evaluated using three commercially available and two patient-derived GBM cell lines. Cell viability was analyzed using MTT assay, whereas alterations in MGMT methylation level were determined using MS-HRM method. The impact of COXIBs, in the presence and absence of TMZ, on Wnt pathway was measured on the basis of the expression of β-catenin target genes. Cell cycle distribution and apoptosis analysis were performed using flow cytometry. COX-2 and PGE2 EP4 receptor expression were evaluated using Western blot analysis. Results Wnt/β-catenin pathway was attenuated by COXIBs and 2,5-DMC irrespective of the COX-2 expression profile of the treated cells, their MGMT methylation status, or radio/chemoresistance. Celecoxib and 2,5-DMC were the most cytotoxic. Cell cycle distribution was altered, and apoptosis was induced after the treatment with celecoxib, 2,5-DMC, etori- and valdecoxib in T98G cell line. COXIBs and 2,5-DMC did not influence MGMT methylation status, but inhibited COX-2/PGE2/EP4 pathway. Conclusions Not only celecoxib, but also 2,5-DMC, etori-, rofe- and valdecoxib should be further investigated as potential good anti-GBM therapeutics.